TINDAKAN SILVIKULTUR PADA HUTAN RAKYAT DI KECAMATAN LANGOWAN SELATAN, KABUPATEN MINAHASA - Viena Angel Sarajar; Hard Napoleon Pollo; Reynold P. Kainde (COCOS, 2022)
Abstract Community forests in North Sulawesi have played a significant role in meeting various needs for wood, ranging from firewood, building materials and other uses. The problem with community forest management in the study area is the inadequate knowledge of farmers about the importance of silvicultural measures in an effort to accelerate stand growth/increment. The purpose of this study was to determine the knowledge of farmers' abilities regarding the application of silvicultural measures and their application. This study uses the interview method to public knowledge about the importance of silvicultural action. The villagers of Winebetan, Kawatak, Kayuuran Atas, Noongan in the Community Forest area in South Langowan District, Minahasa Regency have partly understood the purpose of silvicultural actions in managing community forests. Where this can be seen from the application of silvicultural actions that have been carried out in order to utilize land to get maximum results from community forest management. Keywords: Community Forest, Community Forest Management, Silvicultural Action